Association between collapse and serum creatinine and electrolyte concentrations in marathon runners: a 9-year retrospective study. (23rd September 2020) - Fitzpatrick, Daniel; Walter, Edward; Leckie, Todd; Richardson, Alan; Stacey, Mike; Hunter, Alex; Short, Steve; Hill, Neil; Woods, David; Grimaldi, Rachael; Galloway, Rob; Hodgson, Luke
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Abnormal biochemical measurements have previously been described in runners following marathons. The incidence of plasma sodium levels outside the normal range has been reported as 31%, and the incidence of raised creatinine at 30%. This study describes the changes seen in electrolytes and creatinine in collapsed (2010–2019 events) and noncollapsed (during the 2019 event) runners during a UK marathon. Methods: Point-of-care sodium, potassium, urea and creatinine estimates were obtained from any collapsed runner treated by the medical team during the Brighton Marathons, as part of their clinical care, and laboratory measurements from control subjects. Results: Results from 224 collapsed runners were available. Serum creatinine was greater than the normal range in 68.9%. About 6% of sodium results were below, and 3% above the normal range, with the lowest 132 mmol/l. Seventeen percent of potassium readings were above the normal range; the maximum result was 8.4 mmol/l, but 97% were below 6.0 mmol/l. In the control group, mean creatinine was significantly raised in both the collapse and control groups, with 55.4% meeting the criteria for acute kidney injury, but had resolved to baseline after 24 h. Sodium concentration but not the potassium was significantly raised after the race compared with baseline, but only 15% were outside the normal range. Conclusion: In this study, incidence of a raised creatinine was higher than previously reported. However, the significance of such a rise remains unclear with a similar rise seen in collapsed and noncollapsed runners, and resolution noted within 24 h. Abnormal sodium concentrations were observed infrequently, and severely abnormal results were not seen, potentially reflecting current advice to drink enough fluid to quench thirst.